DESIGN OF ENEMY DESTROYER KAMIKAZE DRONE BY DIPOLE_31 TECHNOLOGY - Nur Rachman Supadmana Muda; Ridwan Asri Sudarsono (JURNAL PENGABDIAN MANDIRI, 2024)
The research aims to design and develop a kamikaze drone Dipole_31 prototype based on the ESP32 microcontroller designed as a high-precision long-range enemy target destruction system. The drone was created to focus on high performance and operational efficiency, making it suitable for targeted destruction missions. The research method uses a structured experimental approach to test various key parameters, such as maximum range, flight speed, flight duration, accuracy of attack on the target, blast impact radius, and overall destructive power. The main components of the drone include the ESP32 microcontroller as a control center, brushless motors for propulsion, GPS modules for navigation, and transmitters and receivers for remote control. In addition, fuzes or explosives are installed to ensure the effectiveness of target destruction. The test results show that this kamikaze drone is capable of flying up to a distance of 150 km with a maximum speed of 500 km/h and a flight duration of 120 minutes. The blast radius reached 50 meters, and the drone showed a target accuracy of 99%, with a margin of error of only 1% from 10 tests.The results of this study show that the design of kamikaze drones has met the established technical specifications and has high operational application potential for long-range destruction missions. This drone combines advanced control and navigation technology with reliable destructive capabilities, making it an effective strategic solution in modern military technology